(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study aims to determine the effect of a toll-like receptor 7/8 (TLR7/8) ligand on the motility of putative X- and Y-chromosome-bearing sperm in rams. Materials and Methods: Sperm from three fertile rams were incubated with tris-citrate buffer containing 0 to 0.9 µM resiquimod (a TLR7/8 ligand) that affects only the X chromosome sperm. Sperm was then subjected to a swim-up test method. After incubation, sperm in the top and lower layers of the media were transferred into a separate new tube. Sperm motility characteristics, concentration, morphometry, and adenosine triphosphate (ATP) concentration from both layers were identified. The data were analyzed for multiple comparisons using one-way analysis of variance. Results: The study demonstrated that the presence of resiquimod used in the swim-up method facilitated the morphometric separation of smaller sperm, predominantly representing Y chromosome sperm in the top layer. Meanwhile, larger samples, indicating X chromosome sperm, accumulated in the lower layer of the media, thus increasing sperm concentration. Resiquimod also decreased motility in the lower layer, but samples in the top layer were unaffected. This decrease was reinforced by the depletion of the ATP level of sperm at the lower level. Conclusion: The TLR7/8 ligand reduced the motility of the putative X-sperm by decreasing their ATP content, allowing separation from the putative Y-sperm. These results suggested the importance of TLR7/8 as a potential biomarker in sperm selection technology. J. Adv. Vet. Anim. Res., 11(3): 648–654, September 2024 http://doi.org/10.5455/javar.2024.k814